Placental Malaria Diagnosis and Risk of Neonatal Anemia: A Comprehensive Review - Sukinah Abd rab Alhassan Alzoori et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Placental malaria (PM) is a significant complication of malaria during pregnancy, caused primarily by Plasmodium falciparum. This condition leads to sequestration of infected erythrocytes in the placenta, causing inflammation and reduced nutrient exchange, which can result in neonatal anemia, low birth weight, and adverse pregnancy outcomes. Diagnosing placental malaria remains challenging due to its asymptomatic nature in many cases. This review explores the diagnostic techniques for placental malaria, its pathophysiology, and the association between PM and neonatal anemia. It also examines current preventive and therapeutic strategies to mitigate these complications, referencing recent studies. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/264 https://doi.org/10.5281/zenodo.14270481